2014
DOI: 10.1021/np400607k
|View full text |Cite
|
Sign up to set email alerts
|

Berberine and Its Metabolites: Relationship between Physicochemical Properties and Plasma Levels after Administration to Human Subjects

Abstract: Berberine (1) is an alkaloid used widely in the treatment of several diseases. However, its physicochemical properties, pharmacokinetics, and metabolism remain unclear, and conflicting data have been reported. In this study, the main physicochemical properties of 1 and its metabolites were evaluated, including lipophilicity, solubility, pKa, and albumin binding. A sensitive HPLC-ESIMS/MS method was developed and validated to identify 1 and its main metabolites in human plasma. This method was used to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 27 publications
1
83
1
1
Order By: Relevance
“…Plasma samples were collected at intervals of 0, 0.083, 0.167, 0.25, 0.5, 1, 1.5, 2, 3,6,8,12, and 24 h after oral administration and centrifuged at 5000×g for 10 min to separate the plasma. Another six SD rats were housed in metabolic cages with free access to water and food and intragastrically administered with BRB (40 mg/kg) once.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma samples were collected at intervals of 0, 0.083, 0.167, 0.25, 0.5, 1, 1.5, 2, 3,6,8,12, and 24 h after oral administration and centrifuged at 5000×g for 10 min to separate the plasma. Another six SD rats were housed in metabolic cages with free access to water and food and intragastrically administered with BRB (40 mg/kg) once.…”
Section: Methodsmentioning
confidence: 99%
“…As a major component of RC, BBR has drawn extensive attention recently because of its wide range of effects such as antiinflammatory, lipid-lowering, anti-tumor, and anti-diabetic effects, among others [2][3][4][5] . In vivo studies have revealed that berberrubine (BRB) is the primary metabolite of 9-demethylated BBR that may have potential pharmacological activities [6] . In fact, BRB showed good antibiosis [7] , anti-inflammatory effects [8] , in addition to antioxidant effect on human fibrosarcoma cells [9] and the scavenging effect of reactive oxidative species (ROS) [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic administration of BBR at 15 mg/kg body weight/day for three months in humans was shown to result in a plasma concentration of 4 nM of BBR [19]. However, > 20 nM of BBR and its metabolites were found in these subjects.…”
Section: Discussionmentioning
confidence: 92%
“…It has been reported that BBR inhibited iNOS expression to attenuate NO production. In addition, several reports have shown that BBR induces antioxidant defence by enhancement of the levels of non-enzymatic antioxidants [15,40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that BBR has abundant pharmacological activities, including antioxidant, anticancer, anti-inflammation, antidepressant, neuroprotection, hepatoprotection, cerebroprotection and cardioprotection [13,14]. In recent years, BBR has been reported to exert beneficial effects in neurodegenerative and neuropsychiatric disorders because of its dual antioxidant and anti-apoptotic activities [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%